Research for educators - Kervin, Lisa.; Vialle, Wilma; Howard, Steven; Herrington, Jan.; Okely, Tony. (Australia : Cengage Learning Australia Pty Limited, 2016)
Research for teachers demystifies the research process and helps teachers appreciate that their role requires this understanding for two reasons: first, they need to be researchers of their own classroom practice; second, they are consumers or research and need to understand how it works in order to know what to trust. Written in accessible and engaging style, Research for educators is an excellent introduction for teachers to the world of research. Read less
Includes glossary and indexes.
Keywords: Education. -- Research -- Methodology; Teachers effectiveness